Agricultural Underdevelopment in Caistor Township - Darnel, Benard W. (My University, 1967)
The purpose of this study is to describe and explain the extent of agricultural underdevelopment in Caistor Township.
Full credit for the author's incentive to investigate this area must go to Dr. L.G. Reeds of McMaster University, who in 1964 conducted a survey of the agricultural conditions in the Niagara Peninsula, on the basis of which a more detailed study of several areas, including Caistor Township, seemed warranted.
The information for this study originated from a variety of sources. The most important of these was direct observations in the field, which after a brief reconnaissance survey in the early part of May, were carried out systematically during the months of June, July, and August of 1966. Interviews were conducted in all parts of the township, in addition an attempt was made to interview all people in four sample block areas. It is estimated that out of a total of 165 interviews, 90 involved the owners of "commercial farms"; other people interviewed were retired farmers, non-farming residents, township officials, clergy men, and store owners.
Field observations provided the basis for the Land Capability Map (Fig.3), for the map showing "Quality of Land use" (Fig. 5), while information about the distribution of non-farm dwellings (Fig . 4) and the location of "Century Farms" (Fig. 2) was obtained from the township office and from a 4-H club member respectively.
Other pertinent data was provided by the Dominion Census Report for 1961, which is the most recent source of information on farm classification, farm income, landuse, and values of agricultural products sold. Finally, the Soil Survey of Lincoln County, and the Physiography of Southern Ontario proved to be useful guides in the assessment of the physiographic conditions of the township.
The methodology employed in this study was selected so as to best facilitate the attainment of the stated objective, but limited time for investigation and lack of sufficient quantitative data about individual farms precluded the use of statistical methods.
The study is divided into eight chapters. Chapters one, three and four deal exclusively with the physical conditions and with related problems, while chapter two gives a brief account of relevant historical factors. Chapters five and six examine the status of agricultural development in the township, the findings of which are evaluated in chapter seven. The final chapter contains the summary and conclusion.
Title: Agricultural Underdevelopment in Caistor Township, Author: Benard W. Darnel, Location: Thode